ANALYSIS OF THE FACTORS THAT INFLUENCE STUDENTS’ LEVEL OF FINANCIAL LITERACY - Mutiarasari Dewi Radityas; Adeng Pustikaningsih (Universitas Negeri Yogyakarta, 2019)
This study aimed to know the influence of Gender, GPA, Year of Study, Residence, Parent’s Education Level (Father), Parent’s Education Level (Mother), Parent’s Income Level, and Work Experience on the Level of Financial Literacy Students of Accounting Education Faculty of Economics YSU 2015-2017. The validity of the instrument used the Product Moment Correlation and instrument reliability using Cronbach Alpha. The data analysis technique used was ordinal logistic regression analysis. The results of this study showed that 1) Gender does not influenced Students’ Level of Financial Literacy; 2) GPA influenced Students’ Level of Financial Literacy; 3) Year of Study influenced Students’ Level of Financial Literacy; 4) Residence does not influenced Students’ Level of Financial Literacy; 5) Parent’s Education Level (Father) does not influenced Students’ Level of Financial Literacy; 6) Parent’s Education Level (Mother) influenced Students’ Level of Financial Literacy; 7) Parent’s Income Level does not influenced Students’ Level of Financial Literacy; 8) Work Experience influenced Students’ Level of Financial Literacy.Keywords: Gender, GPA, Year of Study, Residence, Parent’s Education Level, Parent’s Income Level, Work Experience, The Level of Financial Literacy